A proposition for an integrated church and community intervention to adolescent and youth sexual reproductive health challenges - Magezi, Vhumani (HTS teologiese studies, 2016)
Adolescents and youth in South Africa comprise about 30% of the total population. This phenomenon is referred to as a youth bubble. Research shows that 52% of young people have had full penetrative sex by age 17, and yet 35% of teenagers who have sex say they only sometimes wear a condom, while 32% who have sex say they never wear a condom. Furthermore, studies show that more than half (52%) of parents of teenagers and youth are unaware of their children’s sexual experiences. This situation is insignificantly different between the youth who frequently attend church and those who do not go to church. Responses by churches to the situation have ranged from denialism and hence only maintaining an abstinence stance to superficial youth sexuality discussions that only scratch on the surface. Data indicate that many adolescents seldom have an opportunity to discuss issues of sexual and reproductive health with a caring, knowledgeable adult and are often confronted with unresponsive health services. In response to the situation, there is growing awareness of the important role that religious communities play in adolescents and youth sexual health. The National Adolescent Sexual and Reproductive Health and Rights Framework Strategy (2014–2019) encourage parents and faith-based organisations to bridge this gap by empowering adolescents and youth regarding sexuality issues. The fourth priority of the strategy advocates for a strengthening and scaling up of community networks aimed at supporting adolescents. The churches, however, are caught in a dilemma where on the one hand they have to uphold (teaching) the biblical moral values of abstinence and at the same time respond to the realities of youth who are engaging in sex. With the church being a subsystem of society, a question that is posed is: how should a constructive engagement between church and society regarding youth sexual reproductive health be done? A practical theological response of the church to adolescents and youth sexual reproductive health (AYSRH) that is dialectic and juxtaposes the church and its distinctive values and at the same time practically responding to realities of the needs of adolescents and youth is proposed. In such a model, an engagement that upholds the sacredness of the church while observing the public role of the church as a community institution is advanced.